Mutant Codebraker: um jogo para auxiliar o ensino de teste de mutação - Junkes, Erasmo (2024)
In software development, ensuring that tools meet their objectives effectively is crucial. To achieve this, various techniques have been developed to ensure the quality of programs, including mutation testing. This proactive approach aims to identify and prevent potential erros in the source code, thereby improving software quality. However, mutation testing requires a solid theoretical understanding and programming skills. The objective of this work was to develop a multiplatform puzzle game that uses playful elements and challenges to facilitate the learning of the fundamental principles of mutation testing. The game is structured in phases, each with two stages: the first focuses on creating mutants and interpreting test cases, while the second focuses on completing test cases and eliminating the created mutants. After each phase, a principle related to the challenge is presented. The development of the game is detailed in this work, which also includes a field study to evaluate its acceptance and use. Results were gathered in a business environment through a questionnaire given to a group of employees who are students in software engineering. The participants reported that Mutant Codebreaker is an effective teaching tool, recommended for both professionals and academics, regardless of their experience in software testing.